Beneficial effects of anthocyanins against diabetes mellitus associated consequences-A mini review - Bhagavathi Sivamaruthi (2018)
© 2018, Hainan Medical University. E-edition Published by Hainan Medical University. All rights reserved. Anthocyanins (ACN) are water-soluble pigments, belonging to flavonoids, and are present in almost all fruits, and vegetables at varying concentration. About 635 ACN were distinguished based on the position and number of methoxyl and hydroxyl moieties in the basic structure of ACN. Pelargonidin, cyanidin, delphinidin, malvidin, peonidin, and petunidin are extensively studied anthocyanidins. The absorption, bioavailability, metabolism, pharmacokinetics, molecular mechanism, and analytical techniques of several phytochemicals were described. The biological benefits (antidiabetic, anti-neuro-disorder, anti-cardiovascular diseases, antigastrointestinal diseases, and disorders) of flavonoids and ACN have been reported. Several in vitro, and in vivo reports demonstrated that ACN-rich plant extracts ameliorate the diabetes-associated consequences by reducing the glucose absorption, ROS production, oxidative stress, glomerular angiogenesis, lipid synthesis, and FoxO1 and adipose triglyceride lipase expressions, and improve the insulin secretion, insulin sensitivity, glucose tolerance, glucose uptake, glucose consumption, antioxidant activity. The literature search was made in Scopus, Google Scholar, PubMed using the keywords 'anthocyanin' and 'diabetes'. The documents were carefully checked for the relevance to the current manuscript and the selection was made without any chronological restriction. The present manuscript summarizes the updated reports on antihyperglycemic properties of ACN.